Halal Industry in Javanese Culture; Yogyakarta Regional Government Policy in obtaining its economic values - Addi Arrahman; Illy Yanti (State Institute of Islamic Studies (IAIN) Salatiga, 2022)
Yogyakarta is the center of Javanese culture. He became one of the specialregions in Indonesia, because of the uniqueness of history, governmentsystem, culture, customs and customs. The local wisdom that is ownedis a basic principle that is always present in community activities. In thiscondition, the halal industry is growing rapidly, including in Yogyakarta.Therefore, this research article aims to understand the regulatory formatmade by the Yogyakarta government in developing the Halal Industry;second, to explain the approach used by the regional government of theSpecial Region of Yogyakarta in taking advantage of the economic value ofthe halal industry. The author analyzes the regulatory documents made bythe Yogyakarta regional government, and confirms them with the resultsof in-depth interviews with key informants. This research reveals that theYogyakarta regional government does not make special regulations on theHalal industry, as other regional governments do. However, the culturalapproach used is quite effective in forming a halal business ecosystem thatprovides economic benefits for the community and business actors.